Polyurethanes modified by hydroxyapatite as biomaterials - Król, P.; Król, B.; Pielichowska, K.; Szałański, P.; Kobylarz, D. (Polimery, 2015)
Polyurethane composites were obtained in the reaction of HDI or HMDI diisocyanate, polycaprolactone diol and 1,4-butanediol in 1,4-dioxane solution containing dispersed hydroxyapatite. The distribution of hydroxyapatite particles in the polymer matrix has been examined using SEM-EDX method. By applying DSC, TOPEM DSC and WAXD methods the thermal properties and effect of hydroxyapatite on the crystallization ability of linear polyurethane in the form of thin film have been investigated. With regard to the possibility of using the obtained composite as a biomaterial its mechanical and thermal properties have been determined. Also, the chemical character of the obtained coating and its hydrolytic resistance during long-term incubation in physiological fluid have been evaluated.